The Graphical Information in Sustainability Reports and Corporate Performance: A Southeast Asian Case Study - Wiwik Utami; Erna Setiany; Nurul Hidayah; Zubir Azhar (Universitas Pendidikan Ganesha, 2023)
The primary objective of this study is to evaluate the graphical information quality within sustainability reports produced by companies in Southeast Asia that voluntarily disclose such reports. Additionally, the research delves into examining the correlation between graphical sustainability reporting and corporate performance, encompassing both financial and market-based indicators. The study focuses on companies in Southeast Asia that submit sustainability reports through the global reporting portal (www.globalreporting.org). A total of 132 sustainability reports from 33 companies in the Philippines, Malaysia, Singapore, Thailand, and Indonesia were analyzed consistently over the period from 2016 to 2019. The quality of sustainability reports was assessed using the Graphical Information Disclosure Index (GIDI). The findings reveal that, despite a negative impact on accounting-based performance measured by Return on Equity (ROE), the GIDI score exhibits a positive influence on market-based performance. This underscores the significance of graphical information disclosure in sustainability reports, emphasizing its potential impact on enhancing market perceptions and overall corporate performance in the Southeast Asian context.